Educational Intervention on First Aid Management for Children with Epilepsy and Its Impact on Teachers' Knowledge - Dg Karra, Aulya Kartini; Prihatini, Surya; Yusuf, Saldi; Subaedah (Bantayang Omni Cendekia, 2024)
Background: Epilepsy is a neurological disorder that affects the brain, leading to recurrent seizures in one or more parts of the body. Awareness about epilepsy and its proper management is limited among the general public. Objective: This study aimed to assess the impact of educational interventions on teachers' knowledge of first aid management for children with epilepsy. Methods: This quantitative study utilized a Quasi-Experimental design, specifically a one-group pre-test and post-test design. The study sample consisted of 10 teachers, selected through total sampling. Results: The findings indicated that the educational intervention on first aid management for children with epilepsy resulted in a statistically significant increase in teachers' knowledge levels at MIM Tanabangka, as evidenced by a p-value of 0.000. Conclusion: Prior to the educational intervention, teachers' knowledge regarding first aid management of children with epilepsy was moderate. Following the intervention, a significant improvement in knowledge was observed.